Outlook: membrane junctions enable the metabolic trapping of fatty acids by intracellular acyl-CoA synthetases - Fuellekrug, Joachim; Ehehalt, Robert; Poppelreuther, Margarete (Frontiers in Physiology, 2012)
The mechanism of fatty acid uptake is of high interest for basic research and clinical interventions. Recently we showed that mammalian long chain fatty acyl-CoA synthetases (ACS) are not only essential enzymes for lipid metabolism but are also involved in cellular fatty acid uptake. Overexpression, RNAi depletion or hormonal stimulation of ACS enzymes lead to corresponding changes of fatty acid uptake. Remarkably, ACS are not localized to the plasma membrane where fatty acids are entering the cell, but are found instead at the endoplasmic reticulum (ER) or other intracellu¬lar organelles like mitochondria and lipid droplets. This is in contrast to current models suggesting that ACS enzymes function in complex with transporters at the cell surface. Drawing on recent insights into non-vesicular lipid transport, we suggest a revised model for the cellular fatty acid uptake of mammalian cells which incorporates trafficking of fatty acids across membrane junctions. Intracellular ACS enzymes are then metabolically trapping fatty acids as acyl-CoA derivatives. These local decreases in fatty acid concentration will unbalance the equilibrium of fatty acids across the plasma membrane, and thus provide a driving force for fatty acid uptake.